2005
DOI: 10.1002/art.20900
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inhibition of matrix metalloproteinases on cartilage loss in vitro and in a guinea pig model of osteoarthritis

Abstract: Objective. To study the effects of a matrix metalloproteinase (MMP) inhibitor (S-34219) on osteoarthritis (OA) cartilage cultures and in the meniscectomized guinea pig model of OA.Methods. The inhibitory activity of S-34219 on MMPs and aggrecanase was studied by fluorimetry and immunoassay, respectively. The effects of S-34219 on proteoglycan and collagen degradation were studied in cultures of rabbit and human cartilage. Medial meniscectomy was performed on 29 Hartley male guinea pigs, and these animals were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 32 publications
2
59
0
Order By: Relevance
“…Evaluation of these compounds in selectivity assays against various MMPs (MMP-1, 2, 3, 7, 8, 9, 12, and 14) and other related zinc metalloproteinases including TACE and aggrecanase revealed Ͼ20,000 nM selectivity ( Table 1). In contrast, selectivity data on Ilomastat (Table 1) and other broad-spectrum inhibitors reported in the literature indicate that, although potent against MMP-13 activity, the broad-spectrum inhibitors lack selectivity (3,5,33,34). The only other MMP inhibitors with selectivity comparable with that of the MMP-13 inhibitors in the present study are the class of MMP-13 inhibitors recently reported in the literature (21).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Evaluation of these compounds in selectivity assays against various MMPs (MMP-1, 2, 3, 7, 8, 9, 12, and 14) and other related zinc metalloproteinases including TACE and aggrecanase revealed Ͼ20,000 nM selectivity ( Table 1). In contrast, selectivity data on Ilomastat (Table 1) and other broad-spectrum inhibitors reported in the literature indicate that, although potent against MMP-13 activity, the broad-spectrum inhibitors lack selectivity (3,5,33,34). The only other MMP inhibitors with selectivity comparable with that of the MMP-13 inhibitors in the present study are the class of MMP-13 inhibitors recently reported in the literature (21).…”
Section: Discussionmentioning
confidence: 93%
“…MMPs have long been considered excellent targets for treatment of osteoarthritis (OA), and inhibition of their activity has proven to be efficacious in a variety of models of experimentally induced as well as spontaneously occurring disease (2)(3)(4)(5). However, the clinical utility of broad-spectrum MMP inhibitors developed for treatment of OA has been restricted by dose-and duration-dependent musculoskeletal side effects in humans (joint stiffness, inflammation, pain in the hands, arms, and shoulders termed "musculoskeletal syndrome" [MSS]).…”
mentioning
confidence: 99%
“…MMPs is a family of enzymes that contribute to cartilage degradation through degrading extracellular matrix (EMC) while IL-1β is a cytokine that contributes to cartilage degradation by inducing the expression of MMPs and other proteases [3,4]. Previous studies demonstrated that the inhibition of IL-1β or MMP expression using pharmacologic inhibitors exerted beneficial effects on OA [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Several synthetic oral inhibitors of MMPs have been developed. They are effective in vitro and in animal models of OA [23,24]. However, trials in humans have been disappointing, either because of adverse side effects, such as musculoskeletal pain and tendonitis, or because the drugs lacked efficacy.…”
Section: Protease Inhibitors As Targets For Drug Developmentmentioning
confidence: 99%